A model of management academics' intentions to influence values - Moosmayer, Dirk C. (Academy of Management, 2012)
Business schools face increased criticism for failing in the teaching of management studies to nurture their students’ values. Assuming that individual academics play an important role in shaping the value-related influence of business schools, I model management academics’ intentions to influence values. The suggested model encompasses academics’ economic and social values as internal variables, as well as perceived support for attempting to influence values and academic tenure as social and structural variables. A test with empirical data from 1,254 management academics worldwide reveals that perceived external support is most relevant for explaining intentions. Moreover, academics’ social values, but not their economic ones, contribute to an explanation of their intentions to influence values. The results reveal how important it is for academics to believe that their colleagues, higher education institutions, and other stakeholders support their value-related behavioral intentions.